Greetings from Trinidad and Tobago - (:unkn) unknown (Ace Printery, Trinidad, 2009)
An Aerial view of Maracas, one of the most popular beaches in Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beachgoers--Trinidad and Tobago; Beaches--Trinidad and Tobago; Palms--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Mountains--Trinidad and Tobago; Bays--Trinidad and Tobago; Maracas Bay